2018
DOI: 10.25206/1813-8225-2018-162-174-177
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of electrohydraulic effect application of L. A. Yutkin for removal of flares from terminals of plastic details

Abstract: Омский государственный технический университет, г. Омск эКСПеРиМентальные иССлеДовАния применения элеКтРОгиДРаВличеСКОгО эФФеКта л. а. ЮтКина Для УДАления оБлоя С вывоДов плАСтмАССовых ДетАлей В статье представлено описание электрогидравлического эффекта л. а. Юткина. Приведена электрическая схема лабораторной установки для очистки выводов пластмассовых деталей, а также конструкция опытной установки и сменных приспособлений, применяемых для снятия облоя с выводов пластмассовых деталей. Представлены результаты … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the first middle of the XX century, it was found that when a specially formed pulsed high-voltage electric discharge is created inside the liquid volume, high pressures grow in the region of the latter, which can be used in practice. The method of converting electrical energy into mechanical energy is called the electrohydraulic phenomenon [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the first middle of the XX century, it was found that when a specially formed pulsed high-voltage electric discharge is created inside the liquid volume, high pressures grow in the region of the latter, which can be used in practice. The method of converting electrical energy into mechanical energy is called the electrohydraulic phenomenon [1].…”
Section: Introductionmentioning
confidence: 99%